Impact assessment of a primary care physician counseling program for youth population. Issue 46 (18th November 2022) - Kim, Yun-Su; Kim, Shin-Ae
Abstract : This study aimed to investigate the impact of implementing a primary care physician (PCP) counseling program for the youth population with healthcare needs. This quasi-experimental study used a nonequivalent control group pretest-posttest design, and was conducted at Salim Health Innovation Clinic in Seoul between February and October 2019 comprising 46 participating youths (intervention group) and 48 nonparticipating youths (control group). After 6 months of implementation, drinking (alcohol use control) decreased significantly in the intervention group (0.84 points). There was a significant difference in the anxiety level with a decrease of 2.86 and 0.65 points in the intervention and control groups ( P  = .011) respectively. There was also a significant difference in the health responsibility domain ( P  = .04). Moreover, a significant difference in self-efficacy level was found with a mean increase of 0.18 and 0.16 points in the intervention and control groups ( P =  .001), respectively. The youth population is more prone to neglect self-care due to poor physical and mental health status and no hope for the future because of a lack of jobs and rising housing prices. The program reinforces health-promoting behavior for managing stress and practicing eating high-quality meals, regular exercise, and regular health screening, which can help implement continuous and effective healthcare.